Wastewater technologies and environmental treatment proceedings of the ICWTET2020 - Gutierrez, Rosemary M. (Springer proceedings in earth and environmental sciences, 2021)
This proceedings book provides the latest developments on water as a unique resource that can meet the fundamental needs of human beings and ecosystems. Wastewater generated in industrial, commercial, residential and sensible places must take care as it may pollute the ground and surface water if not treated properly. Environmental pollution discharged from industrial, commercial, residential and sensible places must take care as it may pollute the air, water and land if not treated properly. Most of the design and development of wastewater technologies and environmental treatment were unable to take load as there is huge amount of wastewater and environmental pollution that was generating every day. This threatens the sustainable development, and it needs to solve in accurate, reliable, urgent and timely. Our interest is sustainable innovative and technological transfer approaches which can be used available for supporting, operationalizing and delivering sustainable wastewater technologies and environmental treatment. The authors hope that the book covers possible spectrum of wastewater technologies and environmental treatment to high level of environmental protection, clean and green management lessons, identifies the barriers for transformative change and then informs agenda and initiatives for the sustainable development. ICWTET2020 is dedicated to wastewater technologies and environmental treatment, with a focus on the high level of environmental protection. The aim of the ICWTET2020 is to disseminate current knowledge and sustainable development, share experience and lessons learned and stimulate discussion and reflection, thus promoting a sustainable paradigm shift. The final purpose is to contribute transformative change towards sustainable development through dissemination of sustainable wastewater technologies and environmental treatment.